Contemporary cases in U.S. foreign policy from terrorism to trade - Carter, Ralph G. (CQ Press, 2016)
Many actors - from the president and members of Congress to interest groups, NGOs, and the media - compete to shape U.S. foreign policy. This new fifth edition captures this strategic interplay using 15 recent real-world cases, of which four are brand new